2003
DOI: 10.1136/oem.60.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of British farmers

Abstract: Aims: To estimate the prevalence of neurotic symptoms in a sample of British farmers, to investigate whether farming characteristics are associated with psychiatric morbidity, and to test the hypothesis that British farmers have a higher prevalence of depression and thoughts of life not worth living than the British household population. Methods: A total of 425 farmers from Hereford, Norwich, and Preston completed the Revised Clinical Interview Schedule (CIS-R) by computer between March and July 1999. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…Farmers from industrialised countries have been shown to have poorer physical and mental health than the general population,35 36 although there are also reports to the contrary 37 38. Several reasons are suggested for this: ageing, economic difficulties, risk of injuries, work related illnesses, and exposure to pesticides 36.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers from industrialised countries have been shown to have poorer physical and mental health than the general population,35 36 although there are also reports to the contrary 37 38. Several reasons are suggested for this: ageing, economic difficulties, risk of injuries, work related illnesses, and exposure to pesticides 36.…”
Section: Discussionmentioning
confidence: 99%
“…A random sample of farmers was drawn from the Ministry of Agriculture, Fisheries and Food June Agricultural Census lists of agricultural holdings[11], and each farmer could then nominate a further adult on the same farm holding (usually his wife). Seventy-seven per cent of the cohort were still enrolled in May 1998 and of these, 425 (91%) completed the CIS-R by computer between March and July 1999[12]. …”
Section: Methodsmentioning
confidence: 99%
“…However, conclusive data do not exist to indicate whether farmers experience a higher rate of mental health problems as compared with the general population . Although some authors have reported poorer mental health among farmers versus non‐farmers, other research has found lower rates of mental health problems among farmers than among the general population . Therefore, the first aim of our study was to compare the prevalence of mental health problems, in particular psychological distress, between farmers and non‐farmers of rural China.…”
Section: Introductionmentioning
confidence: 99%